Assessment of lornoxicam as a mouth dissolving film in management of post extraction pain-A randomized control trial - M Aparna Vijayan; K P Mahesh; Karthikeya Patil (Wolters Kluwer Medknow Publications, 2022)
Background: Mouth dissolving film (MDF) is a fast-dissolving drug delivery system that provides a practical means to administer drugs not just to special populations with swallowing difficulties but also to the general public. MDFs are novel dosage forms that dissolve and disintegrate quickly within the mouth. Aim: To assess the efficacy of lornoxicam mouth dissolving film as a potent analgesic and drug delivery system and compare it with the aceclofenac tablet in the management of post-extraction pain. Methodology: The study group comprised 60 subjects of either sex of age group 20-50 years who were divided into an experimental group (group A) and a control group (group B). Group A was administered lornoxicam MDF and group B was administered aceclofenac tablets. Pre-treatment and post-treatment pain assessments were recorded using a visual analog scale (VAS) and an oral pain scale (OPS). Results: In a comparison of the mean value of pre-treatment VAS and VAS after 24 h, the percentage of pain reduction in group A was 86.66%, and in group B was 75%. When comparing the mean value of pre-treatment OPS and OPS after 24 h, the percentage of pain reduction in group A was 93.33% and in group B was 75%. These results were statistically significant, with a P value of 0.00 in both groups. Conclusion: Lornoxicam as an MDF showed promising results in managing post-extraction pain. The potential delivery of lornoxicam through the MDF was safe, with better patient compliance, and no reported cases of adverse effects.